math.com
Home    |    Teacher    |    Parents    |    Glossary    |    About Us
Homework Help Practice Ask An Expert Calculators & Tools Games Store
Email this page to a friend Email this page to a friend
Resources
· Cool Tools
· Formulas & Tables
· References
· Test Preparation
· Study Tips
· Wonders of Math
 
Search
Custom Search



Math Jobs


  
Derivative e^x
(Math | Calculus | Derivatives | Table Of | e^x)
(d/dx) e^x = e^x



Proof of (d-dx) e^x : by (d-dx) ln(x)

Given : (d-dx) ln(x) = 1/x; Chain Rule; d/dx x = 1.
Solve:

(1) (d-dx) ln(e^x) = (d-dx) x = 1
(d-dx) ln(e^x) = (d/du) ln(u) (d-dx) e^x (Set u=e^x)
= 1/u (d-dx) e^x = 1/e^x (d-dx) e^x = 1 (equation 1)
(d-dx) e^x = e^x       Q.E.D.

  
 
  

 
Contact us | Advertising & Sponsorship | Partnership | Link to us

© 2000-2005 Math.com. All rights reserved.     Legal Notices.     Please read our Privacy Policy.